Studi Kasus: Asuhan Keperawatan Jiwa dengan Terapi Kreasi Seni Menggambar terhadap Pasien Harga Diri Rendah (HDR): Case Study: Psychiatric Nursing Care with Art Therapy Drawing for Low Self-Esteem (LSE) Patients. - Indri Sarwili; Ahmad Rizal; Mita Malinda (MPI Press, 2021)
Introduction: The prevalence of severe mental disorders in Indonesia is 1.7 permil exceeding the world ratio of only 1 per mile. The number of cases of low self-esteem at the research site is 25%. How to increase self-esteem in clients one of them is with environmental therapy in the form of drawing creation therapy. Objectives: This study aims to find out the increase in client's self-esteem after being given art drawing creation therapy. Method: This research is qualitative research with case study design using nursing process approach. Participants in this study were Mrs. S. Sampling techniques used were purposive sampling. The research was conducted at Laras X Orphanage in October 2020. Data collection is conducted with interviews, observations and documentation studies. Research instruments are researchers themselves with the help of assessment guidelines and daily activity schedule. Result: After being given therapy for 4 meetings the client showed significant progress by attending therapy sessions until completion and willing to interact with other residents, showing eye contact while communicating, and cheerful facial expressions. Conclusion:The main nursing problem in Mr. S is low self-esteem.